Casework with carers: what works and why?: a longitudinal realist evaluation - Victor, Elizabeth (2017)
Carers who look after family members on an unpaid basis often experience negative impacts from their caring role due to the lack of value placed upon care more widely in society. Casework with carers, ‘the individualised support work undertaken by a practitioner with a newly identified carer’, offers a means to support carers. This thesis considers the research question ‘Casework with carers: what works and why?’. The study places an original focus upon the work of third sector carer organisations upon which there has been very little other research. A comparative perspective is taken to consider this together with the casework with carers undertaken by third sector condition specialist organisations and through statutory carer assessment. The study uses the realist evaluation framework, grounded in critical realism, to identify the outcomes of casework, the mechanisms explaining these and the contextual factors influencing this. A longitudinal research design involving thirty seven qualitative case studies of individual carers’ experiences enabled original findings about change in outcomes over time to be identified and provided a unique insight into the long term impacts of casework. Separate carer and practitioner interviews at timed intervals, supported by audio-recording of the first main contact of casework, provided a comprehensive insight into casework.